2006
DOI: 10.5641/027013606x13080769704361
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Preschool Children's Physical Activity: The Observational System for Recording Physical Activity in Children-Preschool Version

Abstract: In this paper we present initial information concerning a new direct observation system-the Observational System for Recording Physical Activity in Children-Preschool Version. The system will allow researchers to record young children's physical activity levels while also coding the topography of their physical activity, as well as detailed indoor and outdoor social and nonsocial contextual information. With respect to interobserver agreement (IOA), the kappa and category-by-category agreement mean of those ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
132
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(141 citation statements)
references
References 0 publications
3
132
0
6
Order By: Relevance
“…Our findings together suggest the need to promote higher intensity activity as a routine part of the day. 19 Almost all parents reported that their children engaged in some free play activities, typically considered higher intensity. Very few parents reported that their child participated in nonmotorized transportation (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings together suggest the need to promote higher intensity activity as a routine part of the day. 19 Almost all parents reported that their children engaged in some free play activities, typically considered higher intensity. Very few parents reported that their child participated in nonmotorized transportation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Such patterns include: seasonal variations 13 , daily variation (weekday vs. weekend day) 13 , within day variation (morning vs. evening) 14,15 , hourly variation 16 , activity location (indoor vs. outdoor) 17 , how activity is accumulated throughout a day (clustered vs. isolated spurts) 18 , and type of activity during preschool. 19 Detailed information about daily patterns of activity types, prevalence of different activity types, and hourly variability in physical activity and sedentary behaviors among young children is only beginning to emerge.…”
mentioning
confidence: 99%
“…Le Total Motor Score (TMS : 0-6 points) a été calculé. L'intensité PA, le contexte, la composition du groupe et le type d'activité (assise, accroupie, à genoux) ont été directement observés avec une version modifiée de l'OSRAC-P (Observational System for Recording Physical Activity in Children -Preschool Version) (Brown et al 2006) (Numminen, 1995), ein Testhandbuch für die Evaluation von wahrnehmungsmotorischen und motorischen Basisfähigkeiten bei Vorschulkindern, benutzt. Die Total Motor Score (TMS; 0-6 Punkte) wurde auch errechnet.…”
unclassified
“…Die Total Motor Score (TMS; 0-6 Punkte) wurde auch errechnet. Die PA-Intensität, der Kontext, die Gruppenzusammensetzung und die Aktivitätsart -‚sitzend', ‚kauernd' oder ‚kniend' -wurden mit einer direkten, von der OSRAC-P (Observational System for Recording Physical Activity in ChildrenPreschool Version) (Brown et al 2006) La actividad física (AF), su lugar, las interacciones sociales y las habilidades motoras fundamentales fueron investigados en niños finlandeses de 4 años en la guardería. Seis habilidades en estabilidad, habilidades locomotoras y manipulativas fueron evaluadas en 53 niños (24 niños, 29 niñas, antropometría normal) con APM-Inventory Manual para evaluar las habilidades perceptuales y fundamentales motoras en niños (Numminen, 1995) y Total Motor Score (TMS; 0-6 puntos).…”
unclassified
See 1 more Smart Citation